Catatonia in Psychotic Patients: Clinical Features and Treatment Response - England, Mary L. (2011)
We report clinical features and treatment response in 25 patients with catatonia admitted to an inpatient psychiatric unit specializing in psychotic disorders. ECT, benzodiazepines, and clozapine had beneficial effects on catatonic features, while typical antipsychotics resulted in clinical worsening.